Gas phase deposition of well-defined bimetallic gold-silver clusters for photocatalytic applications. Issue 14 (20th March 2023) - Chinnabathini, Vana Chinnappa; Dingenen, Fons; Borah, Rituraj; Abbas, Imran; van der Tol, Johan; Zarkua, Zviadi; D'Acapito, Francesco; Nguyen, Thi Hong Trang; Lievens, Peter; Grandjean, Didier; Verbruggen, Sammy W.; Janssens, Ewald
Abstract : Composition-tuned bimetallic AuAg gas-phase clusters deposited on TiO2 show a remarkable photocatalytic efficiency for self-cleaning applications and a low polydispersity facilitating their characterization. Abstract : Cluster beam deposition is employed for fabricating well-defined bimetallic plasmonic photocatalysts to enhance their activity while facilitating a more fundamental understanding of their properties. Au x Ag1− x clusters with compositions ( x = 0, 0.1, 0.3, 0.5, 0.7, 0.9 and 1) spanning the metals' miscibility range were produced in the gas-phase and soft-landed on TiO2 P25-coated silicon wafers with an optimal coverage of 4 atomic monolayer equivalents. Electron microscopy images show that at this coverage most clusters remain well dispersed whereas EXAFS data are in agreement with the finding that the deposited clusters have an average size of ca . 5 nm and feature the same composition as the ablated alloy targets. A composition-dependant electron transfer from Au to Ag that is likely to impart chemical stability to the bimetallic clusters and protect Ag atoms against oxidation is additionally evidenced by XPS and XANES. Under simulated solar light, Au x Ag1− x clusters show a remarkable composition-dependent volcano-type enhancement of their photocatalytic activity towards degradation of stearic acid, a model compound for organic fouling on surfaces. The Formal Quantum Efficiency (FQE) is peaking at the Au0.3 Ag0.7 composition with a value that is twice as high as that of the pristine TiO2 P25 under solar simulator. Under UV the FQE of all compositions remains similar to that of pristine TiO2 . A classical electromagnetic simulation study confirms that among all compositions Au0.3 Ag0.7 features the largest near-field enhancement in the wavelength range of maximal solar light intensity, as well as sufficient individual photon energy resulting in a better photocatalytic self-cleaning activity. This allows ascribing the mechanism for photocatalysis mostly to the plasmonic effect of the bimetallic clusters through direct electron injection and near-field enhancement from the resonant cluster towards the conduction band of TiO2 . These results not only demonstrate the added value of using well-defined bimetallic nanocatalysts to enhance their photocatalytic activity but also highlights the potential of the cluster beam deposition to design tailored noble metal modified photocatalytic surfaces with controlled compositions and sizes without involving potentially hazardous chemical agents.